Bargaining power and budget ratcheting: Evidence from South Korean local governments. (November 2021) - Choi, Youn-Sik; Kim, Mi-Ok; Jung, Hyung-Rok; Cho, Hyungjin
Abstract: Using the actual and budgeted expenditure data of 241 South Korean local governments from 2010 to 2015, we find that budget decreases in the case of underspending are larger than budget increases in the case of overspending, which is in contrast to the asymmetric budget ratcheting pattern documented in prior studies. More importantly, we find that budget increases in the case of overspending are stronger when government officials have greater bargaining power as proxied by local governments located in the metropolitan area, having greater fiscal independence, and being affiliated with the ruling party. In the case of underspending, budget decreases are larger for local governments in metropolitan areas but do not differ for levels of fiscal independence and the political affiliations of local government heads. Our findings imply that the patterns of budget ratcheting could be diverse based on how local government officials strategically respond to the dynamics between bargaining power and the pressure of justifying budgets. We suggest that "justifying budgets" could safeguard public resources from inefficient budgeting.